Effect of compact thermosyphon height on boiling curve and thermal performance: a visualization analysis - Qin, Siyu (2024)
The thermal management requirement of the servers for data centers has become an urgent issue to be addressed. The two-phase compact thermosyphon has been one of the highly-efficient passive cooling devices to solve heat dissipation problems. In this study, compact thermosyphons with different heights (20 mm, 25 mm, and 50 mm) and filling ratios (25 % − 75 %) were investigated. The corresponding boiling curves and thermal performance were analyzed. Thermal resistance was defined to evaluate the thermal performance in the thermosyphon system. The experimental results illustrate that the reduction in height significantly influences the thermal behaviors of the compact thermosyphon. For the 20 mm height case, the bubble adheres to the condensation surface for a longer time compared with the other cases, which increases the entire bubble growth period. Boiling curves of compact thermosyphons with different heights and filling ratios exhibit distinct characteristics. The heat flux on the boiling surface (qb) with 20 mm height at the low filling ratio (FR = 25 %) is 68.2 % of that with the 50 mm height, indicating the reduced boiling intensity. Both the delayed onset of boiling (ONB) and bubble films of large areas on the condensation surface are generated at FR = 75 % case with 20 mm height, which weakens the phase change heat transfer. For the 50 mm height case, a medium filling ratio and lower input heat flux provide the optimized performance (0.36 K·W−1 of the thermal resistance). For the compact thermosyphon with lower height, low and medium filling ratios are preferred to minimize the deterioration of thermal performance. The outcomes are hoped to provide references for the optimal design and operation of the compact thermosyphon applied in the areas of thermal management and energy conservation.